Liberalism Safe for Catholicism?, A : Perspectives from The Review of Politics - Philpott, Daniel, 1967- (Book collections on Project MUSE., 2017)
This volume is the third in the ""Perspectives from The Review of Politics"" series, following The Crisis of Modern Times, edited by A. James McAdams (2007), and War, Peace, and International Political Realism, edited by Keir Lieber (2009).